»Vis mig dine fanger ...« – et indblik i Grønlands indsattepopulation - Annemette Nyborg Lauritsen (Nordisk Tidsskrift for Kriminalvidenskab)
Greenland is expected to get its first closed institution for delinquents in 2018. With this, the idea of Greenland as “the country without prisons” will be history. Yet even before the first closed institution is built, Greenland already ranks among the most punitive countries in Scandinavia with more than 200 inmates per 100,000 population. The current article draws on studies of inmate records to produce a picture of the social characteristics of the Greenlandic prison population. In addition, it examines how the Greenlandic welfare society has dealt with people before they wound up in institutions for delinquents.